The effect of corporate governance on the effectiveness of Russian companies - ЦойРозалина Александровна (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2013)
In this paper the roles of corporate governances in improving efficiency and market value of Russian companies are strictly systemized. Secondly, the research models, considered their contradictions, and discussion with the research of this type are carefully summarized. The main problem is the lack of generally accepted indicators of corporate governance, which makes the researchers to crate and develop their own codes, since the ratings of various investment companies are usually quite expensive and therefore unavailable for most companies. An empirical analysis was made and its results led to the conclusion that the lack of universally accepted rating make companies to focus on the interests of a specific target group of investors, as not all the parameters of corporate governance affects the decision to grant funds.